2016
DOI: 10.15171/apb.2016.049
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Safety Assessment of New Azinesulfonamide Analogs of Aripiprazole using Prokaryotic Models

Abstract: IntroductionOver the last decades the involvement of reactive oxygen species (ROS) in the molecular mechanisms related to psychiatric disorders such as depression or schizophrenia became evident. [1][2][3] In rat models of depression a decreased activity of antioxidant enzymes such as glutathione peroxidase (GSH-Px) followed by increased lipid peroxidation were observed. [4][5][6] Furthermore, in patients with depression the elevated plasma ROS levels were observed to effectively amplify oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The genetic damage caused by aripiprazole at concentrations below 200 μM was much less than cisplatin, indicating that it could be studied more widely due to its low genotoxicity. The results of our findings in this regard coincided with the work of other researchers (22,23) . The mutagenic and antimutagenic effects of some quinoline-and isoquinolinesulfonamide analogs of aripiprazole were evaluated and their…”
Section: Mtt Assaysupporting
confidence: 93%
See 1 more Smart Citation
“…The genetic damage caused by aripiprazole at concentrations below 200 μM was much less than cisplatin, indicating that it could be studied more widely due to its low genotoxicity. The results of our findings in this regard coincided with the work of other researchers (22,23) . The mutagenic and antimutagenic effects of some quinoline-and isoquinolinesulfonamide analogs of aripiprazole were evaluated and their…”
Section: Mtt Assaysupporting
confidence: 93%
“…The IC 50 of aripiprazole on MKN45 cell line and NIH3T3 cell line was calculated 21.36 μg/mL and 54.17 μg/mL respectively. However, the IC 50 of cisplatin on MKN45 was 12.49 μg/mL and on NIH3T3 results showed that newly synthesized azinesulfonamide analogs of aripiprazole might be considered as genotoxically safe as they do not display mutagenic activity on the tester strains (22) . In addition, genetic toxicity of 545 medications including aripiprazole were studied by using information from 1999 to 2008.…”
Section: Discussionmentioning
confidence: 99%